Future of Islamic insurance (takaful) in Indian market - Syed, Ahmed Salman; Htay, Sheila Nu Nu (2013)
Takaful has been accepted as an alternative to insurance and it becomes popular not only in Muslim countries but also in non-Muslim countries. Similar to the insurance, takaful can provide the same benefit, coverage and protection to the participants. And it has an additional unique feature, i.e. its compliant nature with Islamic principles. India is ranked in the third position in terms of Muslim population in the world. In addition, worldwide India and China accounted for 40% of world's economic growth in the year 2011. According to the World Takaful Report (2009), the annual compounded growth rate of takaful is 31% and Indian sub-continent represents the highest growth of 85% in its Takaful contributions. Furthermore, takaful products are meant for both Muslims and non-Muslims. It is believed that if India is offering takaful products, it will be able to attract more Muslim participants while fulfilling the needs of non-Muslims. Therefore, it is expected that India can be the future takaful giant market. The regulators and the current insurance operators in India should relook at the needs and the trends of the market to take the opportunity of Indian growing economy and takaful unique nature.